Agglomeration and innovation - Gerald Carlino; William R. Kerr (Bank of Finland, 2015)
This paper reviews academic research on the connections between agglomeration and innovation. We first describe the conceptual distinctions between invention and innovation. We then discuss how these factors are frequently measured in the data and note some resulting empirical regularities. Innovative activity tends to be more concentrated than industrial activity, and we discuss important findings from the literature about why this is so. We highlight the traits of cities (e.g., size, industrial diversity) that theoretical and empirical work link to innovation, and we discuss factors that help sustain these features (e.g., the localization of entrepreneurial finance).
URN:NBN:fi:bof-201512111472
Keywords: J2; J6; L1; L2; L6; O3; R1; R3; 330